Hubungan Perilaku dengan Kejadian Karies Gigi pada Siswa/Siswi Kelas IV di MIN 25 Aceh Besar - Nadia Balkis; Fauziah Fauziah; Yusrika Yusrika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
In a study conducted at MIN 25 Aceh Besar, it was found that dental caries problems often occur in class IV students, with a significant influence from the lack of adequate knowledge, attitudes, and actions related to oral health. This cross-sectional analytic design study involved all fourth grade students as samples, totaling 72 people. Data were collected on May 2 and analyzed using univariate and bivariate methods with the chi square test. The results showed that most of the respondents had dental caries, where 39 out of 72 students (54.2%) suffered from the condition. The majority of respondents' knowledge about oral health was in the poor category, where 28 out of 72 students (38.9%) showed a low level of knowledge. This also applies to respondents' attitudes and actions, where 42 students (58.3%) have attitudes that are less supportive of good dental health and 46 students (63.9%) show ineffective actions in maintaining their oral health. Based on these data, there is a significant relationship between behavior (knowledge, attitude, and action) and the incidence of dental caries among these students, with the ρ value for knowledge being 0.003, attitude being 0.006, and action being 0.001. This shows that effective education and counseling on oral health is needed. As a recommendation, it is advisable for schools to collaborate with the local Health Office and Puskesmas to hold regular oral health counseling programs. In addition, establishing a healthy canteen at school can be another preventive measure so that students can choose healthier snacks that support good oral health.